Criminal and criminal actions against minors - Polii, Johanis L.S.S. (Gema Wiralodra, 2023)
This abstract conveys the importance of protecting children's rights as part of citizens. Every country in the world must provide adequate care and protection for children. This guidance and protection cover the child's overall physical, mental, and social growth and development. Even though there are cases of children involved in criminal acts, the development and protection of children remain the state's responsibility. In recent years, the media has often raised the issue of juvenile delinquency or crimes committed by children. This attracts public attention because children even become perpetrators of crimes. This research uses secondary data from library materials such as books, laws, literature, and journals. The educational punishment system is one form of the punishment system used today. This system pays more attention to children's rights and obligations and provides treatment to promote better integration of children into society. This treatment is carried out by placing children in care or coaching institutions that provide education job training and spiritual aspects to improve children's morals and spirituality so that mental improvement can be carried out more quickly. The rules for implementing juvenile crimes in Indonesia are regulated in the Criminal Procedure Code (KUHP) and Law Number 3 of 1997 concerning Juvenile Courts. In this way, it can be seen how the child punishment system currently applies in Indonesia.